2022
DOI: 10.1111/1756-185x.14422
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution Doppler ultrasound in systemic sclerosis: Analysis of digital arteries and nailfold microvasculature using 18‐5 MHz and 33‐9 MHz probes

Abstract: Introduction Newly developed Doppler techniques enable the sampling of slow vascular flows and the extrapolation of spectral parameters in distal arterioles. The aim of this study was to investigate the role of spectral analysis performed by means of ultra‐high frequency ultrasound (US) in the evaluation of the peripheral vascular bed of systemic sclerosis (SSc) patients. Methods Both hands of 33 patients affected by diffuse cutaneous SSc and 34 volunteers were evaluated with a US machine equipped with 33‐9 MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As for tissue perfusion, it was measured by methods such as change in blood flow with laser Doppler imaging and pulse oximetry. Picasso et al 10 suggested that a newly developed ultrasound technique using ultra‐high frequency has the potential to disclose subtle abnormalities in distal digital arterioles. The study by Bello et al 4 was one of the best‐conducted studies in which blood flow change was set as the primary outcome.…”
Section: Study Sample Size Botox Type and Dosage Results Rp Severity ...mentioning
confidence: 99%
“…As for tissue perfusion, it was measured by methods such as change in blood flow with laser Doppler imaging and pulse oximetry. Picasso et al 10 suggested that a newly developed ultrasound technique using ultra‐high frequency has the potential to disclose subtle abnormalities in distal digital arterioles. The study by Bello et al 4 was one of the best‐conducted studies in which blood flow change was set as the primary outcome.…”
Section: Study Sample Size Botox Type and Dosage Results Rp Severity ...mentioning
confidence: 99%
“…In fact, in addition to its use to assess skin thickness [55], evidence is emerging on this new purpose of ultrasound in SSc. Specifically, in patients with SSc, evaluation of the resistive index (RI) and peak systolic velocity (PSV) of interdigital arteries and nail arterioles using high-resolution ultrasound appears to be of some use in assessing subtle abnormalities in the downstream microvasculature [92]. However, pRI (Proximal Resistive Index) of the interdigital arteries does not seem to contribute to the detection of an ongoing pathological process in the small nail arterioles [92,93].…”
Section: The Emerging Role Of Ultrasoundmentioning
confidence: 99%
“…Specifically, in patients with SSc, evaluation of the resistive index (RI) and peak systolic velocity (PSV) of interdigital arteries and nail arterioles using high-resolution ultrasound appears to be of some use in assessing subtle abnormalities in the downstream microvasculature [92]. However, pRI (Proximal Resistive Index) of the interdigital arteries does not seem to contribute to the detection of an ongoing pathological process in the small nail arterioles [92,93]. In addition, Power Doppler UltraSound (PDUS) may play a role in predicting digital ulcers by detecting ulnar artery occlusion and pathological blood flow in the finger pulp [21].…”
Section: The Emerging Role Of Ultrasoundmentioning
confidence: 99%
“… 22 The peak systolic velocity and distal resistive index obtained from digital arteries and nail fold area using spectral Doppler imaging differentiated the patients with SSc from healthy controls. 23 …”
Section: Introductionmentioning
confidence: 99%